Study on the nonuniform mechanical degradation of membranes considering temperature and relative humidity distribution in proton exchange membrane fuel cells. Issue 2 (17th March 2023) - Liu, Wenqing; Qiu, Diankai; Peng, Linfa; Lai, Xinmin
Abstract: The membrane usually breaks down at a specific local position due to the mechanical degradation caused by nonuniform hygrothermal conditions in proton exchange membrane fuel cells. Many studies have been carried out analyzing the stress and strain on membrane along thickness direction, but few of them considered the stress along the surface. By imposing uneven temperature and water profiles according to experiments and simulation, this study systematically investigated effects of varying temperatures, relative humidity, and gas flow directions on the membrane stress/strain in a comprehensive 3D model. The results proved that nonuniform temperature and water content affect the response of the membrane a lot. Although the membrane at the inlet of the flow field suffers higher stress, the membrane at the outlet is easier to fail because higher humidity leads to lower yield stress. For the operating condition, the stress range of cells under the counter‐flow reactant gas is 0.2 MPa less than those under co‐flow direction. And increasing humidity to near‐saturated condition would reduce the stress range from 1.2 to 0.49 MPa. The study contributes to achieving better fatigue resistance for membranes in terms of controlling anisotropic heat and relative humidity for fuel cells.